Effect of Temperature on Pyrolysis Oil Using High-Density Polyethylene and Polyethylene Terephthalate Sources From Mobile Pyrolysis Plant - Prurapark, Ruktai; Owjaraen, Kittwat; Saengphrom, Bordin; Limthongtip, Inpitcha; Tongam, Nopparat (Frontiers in Energy Research, 2020)
This research aims to study the effect of temperature on pyrolysis oil along with analyzing viscosity, density, proportion of pyrolysis products and performance of each condenser towers of pyrolysis high density polyethylene and polyethylene terephthalate. The results showed that the main product of high density polyethylene resin is liquid and the main product of polyethylene terephthalate resin is solid. The pyrolysis of high density polyethylene resin at 400, 425 and 450ºC produce the amount of oil 22.5, 27 and 40.5 L, respectively. The study found that the temperature at 450ºC was the temperature that give the best pyrolysis oil in the experiment. The viscosity was in the range of 3.287–4.850 cSt. The density was in the range of 0.668-0.740 kg/L. The viscosity and density were increased according to 3 factors: high pyrolysis temperature, number of condensers and longer sampling time. From the distillation at temperatures below 65, 65–170, 170–250 and above 250ºC, all refined products in each temperature range shows the amount of hydrocarbon compounds according to the boiling point.